Penjadwalan Optimal Unit-Unit Pembangkit Dengan Metode Particle Swarm Optimization (PSO)” - Roy Naldo Napitupulu . (Faculty of Engineering, Universitas Tanjungpura, 2018)
Generator scheduling is one of the important things in the operation of the electric power system. The basic goal of optimal scheduling is to regulate the loading of generating units at the lowest possible cost while still taking into account some constraints. The operation of the plant is economically influenced by the magnitude of the load requirements, the characteristics of the plant, the maximum and minimum power capacity limits, the fuel costs for each generating unit, and the transmission network losses from the generator to load. This study aims to obtain the minimum generation costs at a certain loading conditions on the power system with the Particle Swarm Optimization (PSO) method. To see the accuracy of the PSO method, it will be compared with the conventional method, the Lagrange method. Both of these methods are applied to 3 and 6 thermal system units and are solved using Matlab. The results of the Particle Swarm Optimization method simulation show that at a load of 300 MW, the PSO method generates a minimum generation cost of 3652.7491 /hr and transmission losses of 13.0563 MW. While the Lagrange method produces a minimum generation cost of 3659.3403 /hr and transmission losses of 13,4291 MW. From all the case studies that have been conducted, it can be concluded that the Particle Swarm Optimization (PSO) method can find a minimum generation value that is quite good when compared to the Lagrange method for optimal scheduling of generating units or economic dispatch. Keywords: Economic Dispatch, Particle Swarm Optimization, Lagrange, Matlab